• Non ci sono risultati.

Here is a short proof n X k=0 n k n + 2t k+ t −1 = n X k=0 n!(n + t − k)!(k + t)! (n − k)!k!(n + 2t

N/A
N/A
Protected

Condividi "Here is a short proof n X k=0 n k n + 2t k+ t −1 = n X k=0 n!(n + t − k)!(k + t)! (n − k)!k!(n + 2t"

Copied!
1
0
0

Testo completo

(1)

Problem 11509

(American Mathematical Monthly, Vol.117, June-July 2010)

Proposed by W. Stanford (USA).

Let m be a positive integer. Prove that

m2

m+1

X

k=m m2

−2m+1 km



k mk2 = 1 m 2m−1

m

.

Solution proposed by Roberto Tauraso, Dipartimento di Matematica, Universit`a di Roma “Tor Vergata”, via della Ricerca Scientifica, 00133 Roma, Italy.

We first consider identity (4.6) in Combinatorial Identities by H. W. Gould:

n

X

k=0

n k

n + 2t k+ t

−1

= n+ 1 + 2t 1 + 2t

2t t

 .

Here is a short proof

n

X

k=0

n k

n + 2t k+ t

−1

=

n

X

k=0

n!(n + t − k)!(k + t)!

(n − k)!k!(n + 2t)!

= n!(t!)2 (n + 2t)!

n

X

k=0

k + t k

n + t − k n−k



= n!(t!)2 (n + 2t)!

n

X

k=0

(−1)k



−(t+ 1) k



(−1)nk



−(t+ 1) n−k



= n!(t!)2 (n + 2t)!(−1)n



−2(t+ 1) n



= n!(t!)2 (n + 2t)!

n + 2(t + 1) − 1 n



=n+ 1 + 2t 1 + 2t

2t t

 .

The desired sum follows easily from the above identity by taking n = (m − 1)2 and t = m − 1

m2

m+1

X

k=m

m2− 2m+ 1 k−m

 1 k

m2 k

−1

=

m2

m+1

X

k=m

m2− 2m+ 1 k−m

 1 m2

m2− 1 k− 1

−1

= 1

m2

(m−1)2

X

k=0

(m − 1)2 k

 m2− 1 k+ m − 1

−1

= 1

m2 · m2 2m − 1

2(m − 1) m− 1

−1

= 1 m

2m − 1 m

 .



Riferimenti

Documenti correlati

[r]

[r]

[r]

[r]

(American Mathematical Monthly, Vol.118, February 2011) Proposed by Mihaly Bencze (Romania). For a positive integer k, let α(k) be the largest odd divisor

[r]

[r]

[r]